Tobacco leaf infusion (Nicotiana tabacum) for cutaneous myiasis in a dog - I Made Yoga Windu Pradana; Dewa Ayu Windhu Manik Anandagiri; Dewa Ketut Raeyadi Purnama; I Made Bagus Januar Bahari; I Putu Cahyadi Putra (ARSHI Veterinary Letters, 2026)
This case report describes the clinical outcome of a dog with cutaneous myiasis treated with topical tobacco leaf infusion (Nicotiana tabacum). An 8-year-old male local dog from Tabanan, Bali, was presented with a foul-smelling open wound at the base of the tail. Physical examination revealed fly larvae within the wound, and cutaneous myiasis was diagnosed. A 2.5% w/v tobacco leaf infusion was prepared by heating 5 g of dried tobacco leaf simplicia in 200 mL of water at 90°C for 30 min, followed by cooling and filtration. The infusion was applied topically at 3–4 drops into the wound twice daily for 10 days. Manual larval extraction and wound suturing were not performed. Larvae emerged from the wound after topical application. Clinical improvement was observed during follow-up, with scab formation on day 7 and complete wound closure by day 14. No adverse clinical signs were reported during the observation period.